Exchange Rate Fluctuations, Pass-Through, and Market Share. (IMF Working Papers; Working Paper ;, 1989)
When the exchange rate fluctuates and the market exhibits hysteresis, planning horizons of domestic and foreign competitors will matter in determining pass-through as well as relative market shares of these firms. Using the Cournot duopoly model, it is shown that if the foreign exporter is a long-term maximizer relative to the domestic firm, pass-through will be lower and average export penetration higher than otherwise.